The case of Charles Dexter Ward - Lovecraft, H. P. (Howard Phillips), 1890-1937 (Weird fiction, 2020)
Providence, Rhode Island, 1928. A dangerous inmate disappears from a private hospital for the insane, his method of escape baffling the authorities. Only the patient's final visitor, family physician Dr. Marinus Bicknell Willett--himself a piece of the puzzle--holds the key to unlocking The Case of Charles Dexter Ward. A macabre mixture of historical investigation, grave-robbing, and bone-chilling revelation, this newly reissued adaptation artfully lays bare one of H.P. Lovecraft's most horrifying creations.